Integrated Robotics STEM Curriculum Towards Industry 4.0 - P.Y., Jiea; H., Hanipah; S.S.A., Sharifah (International Journal of Human and Technology Interaction (IJHaTI), 2018)
In consideration of future employment in STEM domains, university graduates should be prepared to meet the demands of industry 4.0 – resulting from a fourth industrial revolution. Based on the technological concept of cyber-physical systems and the internet of things, it facilitates – among others - the vision of the smart factory. As a result, robotics education is faced with a large potential field of research, which ranges from the technical development and didactical students’ acceptance or the proof of concept of the terms of learning efficiency. This paper presents a conceptual framework to investigated which kinds of learning outcomes prefer in a robotics education in secondary school STEM curriculum. Building upon the results content analysis, a collaborative STEM curriculum using robotics as a platform was created within the collaborative competition environment. It is expected that the students exposed to the robotics curriculum in secondary school would continue to pursue the engineering course in university. Therefore, this is an important contribution towards a globalized and digitalized working world in terms of industry 4.0.